From digital museuming to on-site visiting: The mediation of cultural identity and perceived value - Deng, Yuanbing; Zhang, Xinhui; Zhang, Bowen; Zhang, Bei; Qin, Jing (Frontiers in Psychology, 2023)
Introduction: Museums are using digital resources to provide online services to the public, and the "digital museuming" boom has started. The mechanism of an online museum visit's impact on willingness to visit on site has become an important issue of widespread concern. Therefore, based on the theory of presence and cognitive-emotional-behavioral theory, this paper introduces perceived value and cultural identity as mediating variables to explore the influence of the digital museuming experience on the willingness to visit on site from the audience's perspective. Method: The questionnaires were distributed using the snowball sampling method, and a total of 429 valid questionnaires were received. Result: The empirical test presents the following results: (1) Virtual reality technology multi-dimensionally expands the digital museuming experience; (2) immersion, interaction, and available experience promote willingness to visit on site; (3) hedonic experience in the process of digital museuming cannot be ignored; (4) perceived value and cultural identity play a mediating role. experience cannot be ignored; (4) perceived value and cultural identity play a mediating role. Discussion: Users' experience of visiting virtual museums, perceived value, and cultural identity influence users' willingness to visit museums in the field, but perceived value does not enhance users' cultural identity, which may be due to the inability of the online experience to increase the depth of the experience.